2022
DOI: 10.1155/2022/9408274
|View full text |Cite
|
Sign up to set email alerts
|

A Fuzzy‐Set Qualitative Comparative Analysis of Factors Influencing Servitization Transformation Performance in Chinese Manufacturing Enterprises

Abstract: The development of manufacturing industry affects the operation of Chinese economy, and it is necessary to study the possible configuration paths of servitization transformation to support sustainable development. Based on previous studies of manufacturing servitization transformation, it is extended to explore multifactor combinations which affects servitization transformation performance. This paper constructs technology-organization-environment (TOE) framework of servitization transformation performance eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…In China, Weng et al [21] previously analyzed the mechanism underlying the negative impact of servitization transformation on enterprise performance from the perspective of financial and marketing differentiation. Xiao [22] further confirmed that the total number of service business types (breadths) involved in enterprises is negatively related to corporate profit margins and market value. (3) Complex relationships and noncorrelations: After the servitization paradox was first proposed, scholars further uncovered more complex relations, including the positive "U" type [23], inverted "U" type [24], saddle type [25] and no correlation [26].…”
Section: Literature Reviewmentioning
confidence: 84%
“…In China, Weng et al [21] previously analyzed the mechanism underlying the negative impact of servitization transformation on enterprise performance from the perspective of financial and marketing differentiation. Xiao [22] further confirmed that the total number of service business types (breadths) involved in enterprises is negatively related to corporate profit margins and market value. (3) Complex relationships and noncorrelations: After the servitization paradox was first proposed, scholars further uncovered more complex relations, including the positive "U" type [23], inverted "U" type [24], saddle type [25] and no correlation [26].…”
Section: Literature Reviewmentioning
confidence: 84%
“…In recent years, TOE framework has been used in the manufacturing industry. For example, TOE framework was used to identify the factors that influence the performance of service transformation in manufacturing firms [14]. TOE framework was used to identify the factors that influence firm's digital innovation [15].…”
Section: Plos Onementioning
confidence: 99%
“…Servitization transformation and upgrading has become an important way for manufacturing enterprises to achieve long-term development and performance improvement (Feng et al, 2021;Gao et al, 2023;Liao et al, 2022). The product-centered manufacturing enterprises have increasingly turned to service-centered ones to provide additional services for their core products to promote user value (Raddats et al, 2019), improve user satisfaction (Qi et al, 2020), or get rid of problems such as intensified market competition and reduced product profits caused by homogeneous products (Nasifoglu Elidemir et al, 2020).…”
Section: Introductionmentioning
confidence: 99%